The characteristics of lower limb muscle strength in elite Japanese athletes: focusing on the difference in sports type and competition season - Imawaka, T.; Kameda, M.; Inaba, Y. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The competition and training environment varies depending on the competition season, i.e., summer or winter, not to mention that it varies depending on sports type. Therefore, physical characteristics of elite athletes are considered to be affected by the competition season as well as the sports. Previous studies have suggested that lower limb muscle strength is an important factor in a variety of sporting activities (1). There have been several reports that have examined lower limb muscle strength for different competitive events, but not in terms of the competition season and sports type. This study aimed at investigating lower limb muscle strength in elite Japanese athletes with a focus on the sports type and competition season.